Participatory Monitoring—A Citizen Science Approach for Coastal Environments - Kasten, Paula; Jenkins, Stuart R.; Christofoletti, Ronaldo A. (Frontiers in Marine Science, 2021)
In this article we share our experiences, results, and lessons learned during the creation of a coastal biodiversity participatory monitoring initiative. Throughout 2019 we delivered 5 training workshops to 51 citizen scientists. We validated citizen science collected data, by checking its similarities against that gathered by specialists. We found high similarity values, indicating that, if proper training is provided, there is a great potential for citizen scientists to contribute biodiversity data with high value. During this process a certain level of variation in data produced by specialists was found, drawing attention to the need for prior alignment among specialists who may offer training for citizens. In addition, despite overall similar results between specialists and participants, some differences emerged in particular parts of the habitat; for example, the bivalve zones presented higher complexity and hence greater challenge. Identifying key challenges for participants is key to developing appropriate citizen science protocols. We here provide preliminary evidence that supports the use of our monitoring protocol to obtain biodiversity data gathered by citizen scientists, assuring its scientific quality. Enhancing participation by citizen scientists is key to further validation of the approach and to effectively expand such protocols to enhance the level of biodiversity data collection. In order to enhance participation, and maintain citizen scientist engagement in the initiative, we recommend new investigations that assess the interests and motivations of the public to take part. It is also fundamentally important to have an effective strategy to communicate the results of participants’ monitoring and their applicability to local and global issues, thus maximizing the continuity of engagement of citizen scientists.